Feminist Digital Humanities - Schreibman, Susan (University of Illinois Press, 2025)
Feminist digital humanities offers opportunities for exploring, exposing, and revaluing marginalized forms of knowledge and enacting new processes for creating meaning. Lisa Marie Rhody and Susan Schreibman present essays that explore digital humanities practice as rich terrain for feminist creativity and critique. The editors divide the works into three categories. In the first section, contributors offer readings that demonstrate how feminist thought can be put into operation through digital practice or via analytical approaches, methodologies, and interpretations. A second section structured around infrastructure considers how technologies of knowledge creation, publication, access, and sharing can be formed or reformed through feminist values. The final section focuses on pedagogies and proposes feminist strategies for preparing students to become critical and confident readers with and against technologies. Aimed at readers in and out of the classroom, Feminist Digital Humanities reveals the many ways scholars have pushed beyond critique to practice digital humanities in new ways. Contributors: Daniela Agostinho, Monika Barget, Jenny Bergenmar, Susan Brown, Tanya E Clement, Katrine Dirckinck-Holmfeld, Jaime Lee Kirtz, Cecilia Lindhé, Laura Mandell, Lisa Marie Rhody, Mark Sample, Susan Schreibman, Andie Silva, Nikki L. Stevens, Ravynn K. Stringfield, Dhanashree Thorat, Nanna Bonde Thylstrup, Kristin Veel, Astrid von Rosen, and Jacqueline Wernimont